2005
DOI: 10.1029/2004jd005426
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of tropical cirrus properties and radiative effects

Abstract: [1] The temperature dependencies of cirrus properties are studied using a dual polarization lidar and Mesosphere Stratosphere Troposphere (MST) radar at the tropical station Gadanki (13.5°N, 79.2°E). Cirrus clouds are generally observed in the altitude region 10 to 18 km, with midcloud temperature in the range À85°to À40°C. The cloud temperature decreases with increase in cloud altitude as expected. The mean cloud thickness is generally in the range 0.7 to 1.7 km. For temperatures in the range À75°to À50°C the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
46
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 58 publications
(109 reference statements)
13
46
1
3
Order By: Relevance
“…Our results are in agreement with Sassen and Comstock (2001) who have also presented the dependence of cloud thickness on mid-cloud temperature. Sunilkumar and Parameswaran (2005) studied tropical cirrus clouds and found that this peak is shifted to lower temperatures, in the range of −50 • to −70 • C. The conclusion of Sunilkumar and Parameswaran (2005) that mid-latitude cirrus clouds are generally warmer and thicker than those over the tropics is in agreement with our results. However, we should keep in mind that the number of samples corresponding to temperatures below −60 • C is limited.…”
Section: Temperature and Thickness Dependencies On Cirrus Optical Prosupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are in agreement with Sassen and Comstock (2001) who have also presented the dependence of cloud thickness on mid-cloud temperature. Sunilkumar and Parameswaran (2005) studied tropical cirrus clouds and found that this peak is shifted to lower temperatures, in the range of −50 • to −70 • C. The conclusion of Sunilkumar and Parameswaran (2005) that mid-latitude cirrus clouds are generally warmer and thicker than those over the tropics is in agreement with our results. However, we should keep in mind that the number of samples corresponding to temperatures below −60 • C is limited.…”
Section: Temperature and Thickness Dependencies On Cirrus Optical Prosupporting
confidence: 82%
“…9b there are indications that the cloud optical depth increases as the mid-cloud temperature increases. Other studies have also investigated the dependence of optical depth on mid-cloud temperature and found that these parameters are connected either linearly (Sassen and Comstock, 2001) or through a second-order polynomial function (Sunilkumar and Parameswaran, 2005;Platt et al, 1987). Finally, the dependence of the ratio of optical depth to thickness (mean extinction coefficient) as a function of mid-cloud temperature is examined.…”
Section: Temperature and Thickness Dependencies On Cirrus Optical Promentioning
confidence: 99%
See 1 more Smart Citation
“…With the 15 increase of the height, the temperatures gradually decrease. According to the previous work (Chen et al, 2002, Sunilkumar and Parameswaran, 2005, Seifert et al, 2007, He et al, 2013, temperature has great impact on linear particle depolarization ratio and extinction coefficient by dominating the crystal shape, number concentration and other microphysics properties of cirrus. Furthermore, the cloud base and top height of the first cirrus layer are 6.02  0.60 km and 8.56  0.69 km, respectively.…”
Section: Case Studymentioning
confidence: 99%
“…Polarization and Raman lidars have been employed to detect geometrical and optical properties of cirrus clouds by applying the methods that have been earlier demonstrated by Ansmann et al (1992). Several key 20 optical parameters such as the extinction coefficient, lidar ratio and depolarization ratio as well as the mid-altitude and the corresponding mid-cloud temperature of cirrus clouds were measured (Sunilkumar and Parameswaran, 2005). The depolarization ratios are considered to be of special importance since are related to microphysics properties of the ice crystals Atmos.…”
Section: Introductionmentioning
confidence: 99%